2020
DOI: 10.1007/s00217-020-03443-w
|View full text |Cite
|
Sign up to set email alerts
|

Sonicated extracts from the Quorn fermentation co-product as oil-lowering emulsifiers and foaming agents

Abstract: This study assessed the impact of sonication on the structure and properties of a functional extract (retentate 100 or R100) from the Quorn fermentation co-product (centrate). In a previous study, we reported that the R100 fraction displayed good foaming, emulsifying and rheological properties. Sonication of a R100 solution led to the breakdown of the large hyphal structures characteristic of this extract into smaller fragments. Foams prepared with sonicated R100 displayed a higher foaming ability than with un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Mycoproteins have great gelling, emulsifying, and foaming properties [387][388][389]. A range of fungal cell membrane lipids, including nucleotides and nucleosides, sterols and sterol esters, phospholipids and lysophospholipids, monoglycerides, diglycerides, and their derivatives, are widely used in the food industry due to their gelling, emulsifying, foaming, and thickening properties [390].…”
Section: Mycoproteinsmentioning
confidence: 99%
“…Mycoproteins have great gelling, emulsifying, and foaming properties [387][388][389]. A range of fungal cell membrane lipids, including nucleotides and nucleosides, sterols and sterol esters, phospholipids and lysophospholipids, monoglycerides, diglycerides, and their derivatives, are widely used in the food industry due to their gelling, emulsifying, foaming, and thickening properties [390].…”
Section: Mycoproteinsmentioning
confidence: 99%
“…These include hydrodynamic cavitation extraction (HCE), microwave assisted extraction (MAE), pulsed electric fields (PEF) and ultrasound assisted extraction (UAE), the working mechanisms of which have been reviewed in-depth in other works. 83–107 Key advantages and drawbacks of these technologies with regards to process operation and product safety/nutrition are summarised in Table 2.…”
Section: Waste-to-protein Sourcesmentioning
confidence: 99%
“…This observation highlights the significance of wetting components in the emulsification and foaming attributes of mycoprotein. Lonchamp et al (2020b) employed sonication to modify the cellular structure, emulsifying, and foaming attributes of mycoprotein's biomass. The results indicated that sonicated mycoprotein emulsions had smaller oil droplets (13.57 lm) compared to sonicated whey protein emulsions (18.61 lm).…”
Section: Emulsifying and Foaming Propertiesmentioning
confidence: 99%
“…Mycoprotein's emulsification and foaming properties are ascribed to surface‐active components, the interfacial tension between oil and water, and fungal mycelia remains (Lonchamp et al ., 2020b). Recent research has demonstrated that mycoprotein is an effective emulsifier and foaming ingredient within the food sector (Murray, 2020).…”
Section: Functional Properties Flavour and Textural Characteristicsmentioning
confidence: 99%